Purification and Characterization of Saccharomyces Eubayanus Killer Toxin: Biocontrol Effectiveness Against Wine Spoilage Yeasts - Ganga-Munoz, M (Elsevier B.V., 2020)
Microbiological contamination by spoilage yeasts species are frequent during winemaking, and biological control using antagonistic yeasts is considered a more beneficial alternative to conventional synthetic antimicrobials. Saccharomyces eubayanus killer toxin (SeKT) was produced and purified in a synthetic optimized medium. Purification procedure allowed the identification of SeKT as protein with an apparent molecular mass of 70 kDa and activity at physicochemical conditions suitable for winemaking process. Purified SeKT reduced the levels of volatile phenols produced by the spoilage yeasts Brettanomyces bruxellensis, Pichia membranifaciens, Meyerozyma guilliermondii and Pichia manshurica in wine-like medium. The putative mode of action of SeKT on sensitive yeast strains comprises cell wall disruption through β-glucanase and chitinase activities as well as necrotic and apoptotic death in a toxin dose dependent manner. Thus, SeKT appears to be a promising biocontrol agent against spoilage yeasts during wine aging and storing. © 2020 Elsevier B.V.